Formal Categories of Excess and Narcosis - Rivola, Fabrizio (E|C, 2024)
The article is concerned with researching how the representation of battle has changed in certain examples of contemporary art, transferring to it characteristics of expression and signification, and thus of effectiveness, similar to those produced by the formal instruments of Baroque painting, while at the same time provoking, from a pathemic-perceptual point of view, through this over-stimulation, the effects of narcosis proposed by Marshall McLuhan. Wölfflin’s formal categories describing the transition to the Baroque style emphasise the characteristics of complexity, depth, spatial openness, pictorialism and luministic effects that are well suited to the challenge posed by the theme of battle, already indicated by Leonardo as the main one for history painting. The effect of perceptive and emotional excess aroused by the style and content is comparable to that of shock with consequent narcosis of the sense involved, contributing to the work’s symbolic effectiveness through somatic remodulation of the spectator.